(untitled) (Journal of Educational Sciences, 2025)
This paper presents an experimental study on typing speed, typing accuracy, user experience and cognitive load of people when typing in Kazakh, Russian and English languages. Kazakhstan’s multilingual environment creates unique challenges for digital communication requiring people to have advanced keyboarding skills in three languages. However, there is lack of research on how such multilingual trends affect the user experience, cognitive load and usability of Kazakh, Russian and English languages in the era of Artificial Intelligence (AI). In this work, we designed an experimental study involving 41 human participants taking typing speed tests in three languages, Kazakh, Russian and English. After completing the typing speed test, participants reflected on the experienced cognitive load for each of the three languages, as well as the tying habits and preferences. The evaluation of the typing speed was performed in words per minute (WPM) metric and typing accuracy was reflected on character error rate (CER) metric. We found that the difference in typing speed and accuracy for three languages was statistically significant, with typing speed for English being 32.53±8.31 WPM that is 1.41 times higher than typing speed for Kazakh 23.04±6.59 WPM and 1.12 times higher than typing speed for Russian 29.15±7.58 WPM. Typing accuracy CER metric showed that participants made more errors when typing in Kazakh than in Russian and English languages. CER for Kazakh equals 5.73±5.00 that is 1.09 times more than 5.24±5.27 CER for Russian and 1.78 times more than 3.22±3.59 CER for English. We also found statistically significant differences in experienced cognitive load by our participants in terms of physical demand, effort and frustration. In addition, the results showed the low usability of keyboard typing in Kazakh language using the Cyrillic alphabet among study participants in comparison to typing in English using the Latin alphabet keyboard layout and typing in Russian using the Cyrillic alphabet layout. Key words: Keyboard Typing Speed, Keyboard Typing Accuracy, Cognitive Load, NASA Task Load Index, Large Language Models (LLMs), Artificial Intelligence (AI), Human-Computer Interaction (HCI).